The Impact of Firm Size and E-commerce Usage on Business Performance on Hospitality Industry: A case of Libya - A. Said, Mohamed Ahmed; Azlinna Binti Aziz, Prof. Madya. Dr. Noor (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The hospitality industry is major service sector in most of developed and developing countries in the world economy, and nowadays many hotels implemented e-commerce for their business models and gained great advantages and increase profitability. This study aims to examine the impact of firm size and e-commerce usage on business performance of hospitality industry in general and hotels in Libya in particular. A quantitative approach was applied on hotel industry in Libya, mainly those hotels that have previous practices and experience with e-commerce. The results shows that small and medium size firms in hospitality industry in Libya are facing similar challenges and obstacles to other small businesses when establishing e-commerce website, and also shows a strong relationship between e-commerce usage and business performance, and high increase in profitability when hotels implement e-commerce and start to conduct online booking